Epidemiological survey of leprosy conducted in metropolitan France between 2009 and 2010 - Bret, S; Flageul, B; Girault, P-Y; Lightburne, E; Morand, J-J (Annales de dermatologie et de vénéréologie, 2013)
There is no official leprosy register in France. The last epidemiological survey on leprosy in metropolitan France was done between 1995 and 1998. We performed a new epidemiological study of leprosy in metropolitan France in 2009 and 2010. We contacted 85 dermatology and infectious disease units by e-mail or by telephone in order to determine the number of leprosy patients either being followed up or newly diagnosed in 2009 and 2010. The response rate was 87%. In 2010, 127 patients were being followed up in metropolitan France, mostly at dermatology units (78%). Seventy-five patients were on anti-bacillary treatment and the prevalence was 0.011/10,000. There were 39 new cases diagnosed in 2009 and 2010 (mean 19 cases/year) (low case-detection rate: 0.003 per 10,000 inhabitants). Among the new cases, seven patients (18%) were of French origin, with two from metropolitan France and five from French overseas territories. Our study confirms the persistence of imported leprosy in France and shows no significant decrease in the number of new cases since 1998 (19 vs. 18 new cases/year) or in disease prevalence (0.013 vs. 0.011 per 10,000 inhabitants). This prevalence is very far removed from the one per 10,000 inhabitants proposed by the World Health Organization as the criteria for endemic disease. Most patients in our survey were immigrants (82%). Lepromatous forms (46%) were more frequent than the tuberculoid forms (33%). All patients had either travelled to or lived in areas of high leprosy prevalence, including metropolitan subjects. Leprosy remains present in metropolitan France, and it is still important to continue teaching about it at medical faculties in order to ensure diagnosis of new patients as early as possible.